A Large Undisturbed Column Method to Study Flow and Transport in Macropores and Fractured Media. Issue 6 (26th April 2019) - Jørgensen, Peter R.; Mosthaf, Klaus; Rolle, Massimo
Abstract: Intact soil columns can bridge the gap between field studies and idealized laboratory investigations of flow and transport in macropores and fractured media. However, the value of intact column studies is often hampered by shortcomings such as lack of column intactness, small column size, and column rim flow, which can cause serious artifacts and hamper system understanding. The flexible‐wall pressurized large undisturbed column (LUC) method overcomes these limitations and is a valuable approach to analyze fluid flow and solute transport in macroporous and fractured geological formations. The method investigates subsurface processes in complex media, mimicking in situ conditions and facilitating the control of system boundary conditions including effective stress. In recent years, considerable experience has been gained through different applications of the LUC approach. Modeling tools have also been developed for a detailed interpretation of flow and transport processes in LUC systems. This paper describes the steps of the LUC method from column excavation in the field to experimental setup in the laboratory. The description encompasses the key features of the sampling of LUCs in field excavations, the laboratory setup, the procedure for hydraulic and transport experiments, as well as practical challenges and potential issues during operation of an LUC system. Application examples with a fully three‐dimensional numerical model of LUC tracer experiments are also presented to illustrate the quantitative interpretation of transport processes in macroporous clayey tills. Abstract : Article impact statement : Illustration, discussion, and modeling interpretation of a unique method to investigate flow and transport in macropores and fractured media.